Pengembangan Karakter Pada Anak Usia Dini (AUD) - Rohmah, Umi (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD), FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2018)
Abstract Qualified characters need to be established and nurtured from an early age. Early age is a critical period for the formation of one's character. The character of early childhood is influenced by two factors, namely internal and external. Early childhood has distinctive characteristics, physically, psychologically, socially, morally, and so on. Character development in school will be done smoothly, if the teacher in its implementation pay attention to some principles of character development. Character is developed through stages: knowledge (knowing), execution (acting), and habit (habit). There are several challenges that become the main problem in character development in the global era. There are some effective tips on developing early childhood characters in the school that can be offered, including: 1) involving the moral aspects of knowing, moral feeling, and moral action, 2) reviving sunnah Dhuha prayers together, 3) kissing the hands of teachers, 4) tell the biography of the characters (5) holding regular prayers and istighosah, 6) teachers, staff, and principals should be role models for children, 7) working with parents, 8) providing rewards and sanctions, etc. The successful development of character in early childhood education can be known from everyday behaviors that appear in every child's activity. Keywords: character development, early childhood